43.4k views
3 votes
I need help with algebra

I need help with algebra-example-1
User Tails
by
5.0k points

2 Answers

5 votes

We are given [ H(x) = A(x) + B(x) - C(x) ]. Substitute with the given functions.

H(x) = (x³ - 5x + 4) + (2x² + 5x - 6) - (-x² + 3)

~Simplify

H(x) = (x³ - 5x + 4) + (2x² + 5x - 6) + (x² - 3)

~Combine like terms

H(x) = x³ + (2x² + x²) + (-5x + 5x) + (4 - 6 - 3)

~Simplify

H(x) = x³ + 3x² - 5

The answer is x³ + 3x² - 5

Best of Luck!

User Milosa
by
4.9k points
5 votes

Answer:

x³ + 3x² - 5

Explanation:

(x³ - 5x + 4) + (2x² + 5x - 6) - (-x² + 3)

x³ - 5x + 4 + 2x² + 5x - 6 + x² - 3

x³ + 3x² - 5

User Josh Butler
by
5.2k points